Effect of processing on the nutritional value of soybean proteins - Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
It has been recognized for many years that some sort of processing of soybeans will yield a product of superior nutritional value. As our understanding of the effects of different processing techniques increases, we will continue to see advances in technology that will yield soybean products of superior nutritional value. The challenge for livestock producers is to recognize the products that offer improved nutritional benefits and to have the wherewithal to use those products when they are economically advantageous.
Keywords: Swine; Processing; Nutrition; Soybean proteins